Uncommon cause for anterior knee pain - Aggressive aneurysmal bone cyst of the patella - Balke Maurice; Dedy Nicolas; Mueller-Huebenthal Jonas; Liem Dennis; Hardes Jendrik; Hoeher Juergen (BMC, 2010)
Abstract A 56-year-old man presented with a two month history of increasing anterior knee pain without previous trauma. As usual we recommended physiotherapy with stretching exercises of the quadriceps muscle. Since symptoms did not improve after 6 weeks MRI was performed. Surprisingly a hyperintense lobulated mass of the patella with small fluid-filled cavities at the inferior pole was revealed. We performed an open biopsy to exclude any malignancy and diagnosed an aneurysmal bone cyst. Further examination with CT scans showed an aggressive behaviour with cortical breakthrough. We performed an intralesional curettage with additional high-speed burring and bone cement packing. Sixteen months later the patient was free from any complaints and without signs of local recurrence. Primary bone tumors of the patella are extremely rare and occurrence of aneurysmal bone cysts in this localization is very uncommon. This case report indicates that although anterior knee pain is a very frequent and usually harmless symptom, it is essential to consider that it might also be caused by more severe disorders such as bone tumors.